CO2 Reduction: From the Electrochemical to Photochemical Approach. Issue 11 (12th September 2017) - Wu, Jinghua; Huang, Yang; Ye, Wen; Li, Yanguang
Abstract: Increasing CO2 concentration in the atmosphere is believed to have a profound impact on the global climate. To reverse the impact would necessitate not only curbing the reliance on fossil fuels but also developing effective strategies capture and utilize CO2 from the atmosphere. Among several available strategies, CO2 reduction via the electrochemical or photochemical approach is particularly attractive since the required energy input can be potentially supplied from renewable sources such as solar energy. In this Review, an overview on these two different but inherently connected approaches is provided and recent progress on the development, engineering, and understanding of CO2 reduction electrocatalysts and photocatalysts is summarized. First, the basic principles that govern electrocatalytic or photocatalytic CO2 reduction and their important performance metrics are discussed. Then, a detailed discussion on different CO2 reduction electrocatalysts and photocatalysts as well as their generally designing strategies is provided. At the end of this Review, perspectives on the opportunities and possible directions for future development of this field are presented. Abstract : CO2 reduction to useful chemical fuels via the electrochemical or photochemical approach represents promising directions to convert and utilize this greenhouse gas molecule. The Review summarizes recent progress on the development, engineering, and understanding of CO2 reduction electrocatalysts and photocatalysts.